Advanced flood prediction at forest with rainfall data using various machine learning algorithms - M.S., Saravanan; S., Sivashankar; A., Rajesh; Mat Ibrahim, Masrullizam (2024)
The aim is to classify and predict floods in advance with rain data patterns of India using spatio-temporal logic. Two Classification algorithms are used to achieve the maximum accuracy namely K-Nearest Neighbour with a sample size=5 and Logistic Regression with a sample size=5 for continues iterations. The work focused towards comparison of K-Nearest Neighbour and logistic regression, which has confidential and forecast the standards from the rainfall statistics to produce estimated accuracy with K-nearest neighbour has higher accuracy by comparing with Logistic Regression accuracy. It has a high accuracy of 50.35%, in comparison with the Logistic Regression algorithm 45.96%. The significant values have been statistically defined with the value of (p< 0.001). Prediction in flood patterns, K-Nearest Neighbour consisting rainfall pattern expressively used to produce improved accuracy than the Logistic Regression.